Pemetaan Tingkat Kerawanan Bencana Tanah Longsor Menggunakan Metode Weighted Overlay di Kecamatan Poncokusumo Kabupaten Malang - Rif'ah, Kunti Dzatir; Jamil, Achmad Maulana Malik; Suwito, Suwito; Kurniawati , Dwi (PT. Pubsains Nur Cendekia, 2024)
Poncokusumo District is a hilly area with steep to very steep slopes. These conditions contribute to a very high landslide potential in Poncokusumo District, making it crucial to conduct further studies on landslide hazard mapping to reduce landslide disaster risk. This research employs a quantitative approach using scoring and Weighted Overlay methods. The study analyzes landslide susceptibility using the Weighted Overlay method. This study analyzes landslide vulnerability using overlay techniques from several maps related to factors affecting vulnerability assessments. The analysis was carried out by combining data on rainfall, slope gradient, soil type, and land use. Based on the analysis results, it was found that the landslide susceptibility level in Poncokusumo District ranges from moderate to very high with an area reaching 22,135.84 hectares. This is primarily due to the steep to very steep slopes.